Resource Mobilization Strategy Report: The Development of a National Framework for Weather, Water and Climate Services for Zambia - International Water Management Institute (2024)
The Resource Mobilization Strategy (RMS) aims to secure funding from various sources to ensure the sustainable operation of NFWCS-ZM in Zambia. This strategy is intended to be a key tool to support the country's funding strategies and provide guidance for funding proposals to sustainably implement NFWCS-ZM.